Chronic oedema: a prevalent health care problem for UK health services - Moffatt, Christine J.; Keeley, Vaughan; Franks, Peter J.; Rich, Anna; Pinnington, Lorraine L. (Wiley, 2016)
Chronic oedema is a major clinical problem worldwide, which has many important secondary consequences for health, activity and participation. Effective treatment planning and organisation of services is dependent on an understanding of the condition and its epidemiology. This cross sectional study was designed to estimate the point prevalence of chronic oedema within the health services of one UK urban population and to determine the proportions that have concurrent leg ulceration. Patients with chronic oedema were ascertained by health care professionals in one acute and one community hospital, all relevant out-patient and community nursing services, general practices and all nursing/residential homes in one urban catchment area (Derby City). The presence and distribution of oedema was confirmed through a brief clinical examination. A battery of demographic and clinical details was recorded for each case. Within the study population of Derby City residents, 971 patients were identified with chronic oedema (estimated crude prevalence 3.93 per 1,000, 95% CI 3.69-4.19). The prevalence was highest amongst those aged 85 or above (28.75 per 1,000) and was higher amongst women (5.37 per 1,000) than men (2.48 per 1,000). The prevalence amongst hospital in-patients was 28.5%. Only 5 (3%) patients in the community population had oedema related to cancer or cancer treatment. Of the 304 patients identified with oedema from the Derby hospitals or community health services 121 (40%) had a concurrent leg ulcer. Prevalence statistics and current demographic trends indicate that chronic oedema is a major and growing health care problem.